Bio-processing of wheat – untapped opportunities for value added products - Nagarajan, Subramaniam (Journal of Cereal Research, 2013)
For more than a century wheat improvement activity in India has been focusing on enhancing the per hectare productivity under varying environments and growing conditions. Much success has been achieved in breeding high yielding stress resilient varieties with grain quality satisfying the domestic needs. From a mere 9.0 milliontons total production during 1947 when India was bifurcated; in 2012 about 93.8 million tons of wheat grain was harvested. In addition to this a huge amount of straw or biomass was also harvested. Till few decades ago, this biomass was utilised as bovine feed to serve more as roughage. Now, with a high degree of farm mechanisationand adoption of the rice wheat system, this resource is burnt in the field so that the field is vacated quickly to transplant rice. The present surging grain surplus and the fall in demand for the biomass has created a need to revisit the wheat improvement activities and to explore the possibility of positioning the wheat crop for total bioprocessing usage at least by 2030. This will then necessitate bringing about a substantial research re-orientation to create a win-win profit situation to both the farmer and the bio-processing industry.